AUDIT DELAY PADA INDUSTRI MAKANAN DAN MINUMAN YANG LISTING DI BEI - Puspita, Dwiny; Diyani, Lucia Ari (Akuntansi Krida Wacana, 2018)
Audit delay was the timeliness in completing the audit of financial statements until the issuance of audit reports. This study aimed to determine the factors that affected audit delay in the food and beverage industry listed on the Indonesia Stock Exchange (BEI) in 2011-2016. This research used logistic regression model. The population in this research were all food and beverage industry listed on BEI. The sampling technique used random purposive sampling so that the sample of research included in the criteria amounted to 11 companies. The results of this study indicated that firm size, DAR, ROA has no effect on audit delay, while the KAP size has a significant negative effect on audit delay.